Welfare and Bargaining Power of Farmers in Bromo-Tengger-Semeru, Agropolitan Area, East Java - Suyanto, Bagong; Adam, Subagyo; Ariadi, Septi (Opción, 2019)
Bromo-Tengger-Semeru is an agropolitan area in East Java, which was devel- oped to encourage the welfare improvement of the local community, especially local farmers who are involved in the cultivation business in the agricultural sector. This study involves 400 farmers in Malang, Probolinggo, Pasuruan and Lumajang, where they participated in interviews. This study found that the problematic situation faced by farmers is funding and efforts to add value to the products they produce are apparently not comparable to the selling price of the product. Most farmers said they would rather sell their raw products. In determining the price of agricultural products, farmers often lose out to mid- dlemen or moneylenders. Currently, the agropolitan area development pro- gram, for local farmers has not been very useful in improving the bargaining position and the level of welfare of local farmers.